UJI EFEKTIVITAS ANTILITHIASIS EKSTRAK ETANOL ALANG-ALANG (IMPERATA CYLINDRICA (L.) BEAUV) PADA TIKUS PUTIH (RATTUS NOVERGICUS) - Stenly - Komansilan; Rolef Rumondor (J-KESMAS: Jurnal Kesehatan Masyarakat, 2022)
Background: Kidneys in the body function as filters to clean blood or other fluids. This function is intended so that the chemicals contained in the blood or other body fluids are not carried back by the blood and circulated throughout the body. Some of this filtered dirt will be excreted through the kidneys with urine and some may be left behind and settles into kidney stones Purpose: The aim of this study was to determine the antilithiation effectiveness of Imperata extracts) Methods: In white rats by looking at the histological picture of the rats' kidneys The study design, the treatment group was divided into 5 groups: Control group (P0), ethylene glycol group (P1), Hydrochlorothiazide treatment group (P2), Imperata extract group with a dose of 100 mg / kgBW ( P3), and the alang-lang extract group at a dose of 200 mg / kgBW (P4) Results: The results showed that Imperata extract had activity in repairing the kidneys of rats with urolithiasis. Conclusion: And the dose of Imperata extract 200 mg / kgBB has better effectiveness